2012
DOI: 10.3109/08958378.2012.708065
|View full text |Cite
|
Sign up to set email alerts
|

The pulmonary deposition and retention of indium-111 labeled ultrafine carbon particles in healthy individuals

Abstract: No evidence for particle translocation from the lungs could be proven 7 days after exposure. It is possible to follow-up Indium-111 labeled UF carbon particles at least 1 month post-administration without increasing the administered activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Regarding this calculation, if PM2.5 is inhaled for 208 days at the maximum value within the environmental standards in Japan, the exposure exceeds the no-observed-adverse-effect level estimated in this study. However, considering that PM2.5 is slowly eliminated from the lung or brain [ 8 , 45 ], long-term exposure over years may be of concern. On the other hand, although air pollution has regional and seasonal characteristics, there are many areas where PM2.5 in the atmosphere is relatively high throughout the year; India’s average PM2.5 concentration level was 75 to over 85 μg/m 3 in 2019 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this calculation, if PM2.5 is inhaled for 208 days at the maximum value within the environmental standards in Japan, the exposure exceeds the no-observed-adverse-effect level estimated in this study. However, considering that PM2.5 is slowly eliminated from the lung or brain [ 8 , 45 ], long-term exposure over years may be of concern. On the other hand, although air pollution has regional and seasonal characteristics, there are many areas where PM2.5 in the atmosphere is relatively high throughout the year; India’s average PM2.5 concentration level was 75 to over 85 μg/m 3 in 2019 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Klepczynska-Nystrom et al 18 reported that about 95% of ultrafine carbon particles were retained in the lung 7 days after exposure. If toner particles are harmful to human lung, the higher the exposure concentrations are, the severer the effects may be on chest x-rays.…”
Section: Chest X-ray Examinationsmentioning
confidence: 98%
“…Concerning the chest x-ray examinations, a total of seven subjects had chest x-rays classified into category 1/0 according to the ILO international classification of pneumoconiosis radiographs through the follow-up period: three subjects in the low exposure group and one subject in the control group in the first survey, one subject in the low exposure group and one subject in the control group in the second survey, and one subject in the low exposure group in the fifth survey. Klepczynska-Nystrom et al 18 reported that about 95% of ultrafine carbon particles were retained in the lung 7 days after exposure. If toner particles are harmful to human lung, the higher the exposure concentrations are, the severer the effects may be on chest x-rays.…”
Section: Chest X-ray Examinationsmentioning
confidence: 99%
See 1 more Smart Citation